Quantum dot contact lens and preparation method thereof
By using ligand-modified quantum dots in contact lenses and preparing them using the hot injection method, the problems of quantum dot aggregation and poor compatibility are solved, a stable, safe and efficient phototherapy effect is achieved, and visual function is improved.
Patent Information
- Application Number
- CN202411583465.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-21
AI Technical Summary
When existing contact lenses use quantum dots for phototherapy, the quantum dots are prone to agglomeration and inactivated, and have poor compatibility with human tissues, resulting in complex operation, high cost and difficult to promote.
Quantum dots modified with ligands are used and prepared by hot injection method to ensure the monodispersity of quantum dots in polymer materials, avoid agglomeration, and improve biocompatibility and fluorescence stability.
The stable dispersing and excellent biocompatibility of the quantum dot is realized, the blue light absorption and red light emission performance of contact lenses are improved, the visual effects are improved, and the complexity and cost of preparation are reduced.
Smart Images

Figure CN119335764A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of contact lenses, and in particular to a quantum dot contact lens and a preparation method thereof. Background Art
[0002] The most common uses of contact lenses (CL) include optical intervention and cosmetic purposes. Other indications include treatment (i.e. corneal lesions, dry eye), diagnosis (i.e. fundus photography, electroretinogram, measurement of biometric parameters of severe corneal disorders), prevention (i.e. exposure keratitis, myopia progression), and occupational (i.e. pilots, police officers, athletes).
[0003] Quantum dots (QD), also known as artificial atoms, are tiny crystals in semiconductor materials. They are usually between 1 and 20 nanometers in diameter and are formed by the interface of two semiconductor materials, the surface of a semiconductor, or the combination of their interfaces. This structure has a very small three-dimensional space inside, which has the characteristics of limiting electrons and electron holes. The charge carried by the electrons inside is an integer multiple of the elementary charge, and the stability is good. When a beam of light shines on the quantum dots, the electrons will be excited to jump to a higher energy level. When these electrons return to their original lower energy level, they will emit a beam of light with a certain wavelength, and then emit fluorescence. At present, in the field of television, the industrialization of quantum dot display has been realized, and the use of quantum light sources has a good visual display effect. In the field of biomedicine, it can be used as a fluorescent marker in disease diagnosis and drug metabolism based on the controllability of its luminescence. According to the characteristics of quantum dot materials, they can be divided into traditional chalcogenide quantum dots and new perovskite quantum dots.
[0004] In a recently published article, researchers pointed out that light can improve mitochondrial function to compensate for the decline in vision in the elderly, which is due to the specific light absorption characteristics of mitochondria, which affect their performance. Mitochondrial density is the largest in photoreceptors, especially in cones, which have high energy requirements and regulate color vision. Due to insufficient mitochondrial aging activity, our vision becomes very easy to decline as we age. Longer wavelengths spanning 650-1000 nanometers increase mitochondrial complex activity, membrane potential, and adenosine triphosphate production, thereby improving the visual function of the elderly. As a non-invasive neuromodulation strategy, light stimulation has shown the potential to alleviate various pathological changes in animal models, such as depression, insomnia, and Alzheimer's disease (AD). For example, in the treatment of insomnia, flickering light stimulation has become a promising non-invasive neuromodulation strategy for relieving neuropsychiatric disorders. Light flickering triggers an immediate and sustained increase in extracellular adenosine levels in the primary visual cortex (V1) and other brain regions (up to 3 hours after flickering). 40 Hz light flickering for 30 minutes can also promote sleep in insomniac children by reducing sleep onset latency, increasing total sleep time, and reducing wakefulness after sleep onset.
[0005] At present, most of the methods used are external irradiation, which uses a fixed light source of a specific wavelength to irradiate the fundus to achieve eye care and treatment. Even if treatment is done through a wearable method such as contact lenses, an auxiliary power supply and signal transmission system are usually used to control the light source irradiation. The above methods are complex, difficult to operate, costly, and have cumbersome preparation processes and are not easy to promote. Summary of the invention
[0006] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide a quantum dot contact lens and a method for preparing the same.
[0007] In a first aspect of the present invention, a quantum dot contact lens is provided. According to an embodiment of the present invention, the quantum dot contact lens comprises a contact lens polymer material body, wherein quantum dots are embedded and distributed in the contact lens polymer material body, and the quantum dots are modified by ligands.
[0008] According to the quantum dot contact lens of the above embodiment of the present invention, it includes a contact lens polymer material body, and quantum dots are embedded and distributed in the contact lens polymer material body. The quantum dots absorb harmful blue light and emit reddish fluorescence at the same time, which is incident into the wearer's eyes, thereby achieving the effect of visual improvement. However, the inventors found that when quantum dots are directly added during the preparation of contact lenses, on the one hand, the quantum dots are easy to agglomerate and lose their activity, that is, they cannot emit fluorescence stably. On the other hand, the compatibility of quantum dots themselves with human tissues is poor. Only by improving the compatibility of quantum dots with eyes can the safety of contact lenses be guaranteed. In view of this, the inventors found that the use of quantum dots modified by ligands can not only improve the dispersibility of quantum dots in polymer materials, avoid the agglomeration of quantum dots, and cause the loss of fluorescence performance, but also the functional groups at the chemical chain ends of the ligands can passivate the effect of dangling bonds on the surface of quantum dots (dangling bonds themselves belong to surface defects of quantum dots, which will reduce the fluorescence properties and chemical stability of quantum dots) when bonding with the surface atoms of quantum dots. Therefore, the passivation of the ligand can reduce the surface defects of quantum dots, inhibit the non-radiative recombination of carriers, and improve the stability and fluorescence properties of quantum dots. At the same time, ligand-modified quantum dots have excellent biocompatibility compared to unmodified quantum dots.
[0009] In some embodiments of the present invention, the particle size of the quantum dots is 1 nm to 20 nm, preferably 4 nm to 7 nm. For example, the particle size is 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 15 nm, 20 nm, etc. The inventors have found that the optical properties of quantum dots are strongly dependent on the size of the quantum dots themselves in addition to being affected by the chemical composition. The smaller the size of the quantum dots, the wider the band gap, and the cutoff response wavelength to the spectrum is blue-shifted (the emission peak moves toward the short wavelength direction); conversely, the size of the quantum dots increases, the band gap narrows, and the cutoff wavelength of the response to the spectrum is red-shifted (the emission peak moves toward the long wavelength direction). Therefore, the present application uses quantum dots with a particle size of 1 nm to 20 nm to achieve absorption of blue light and emission of red light.
[0010] In some embodiments of the present invention, the band gap of the quantum dot is 1.24 eV~2.07 eV. The inventors have found that quantum dots themselves have the characteristics of wide-spectrum excitation and narrow-band emission. Therefore, when the energy value corresponding to the band gap of the selected quantum dot material is lower than the energy of the blue light photon, blue light can be absorbed, and the wavelength of the emitted light of the quantum dot depends on its band gap. Therefore, the present application uses quantum dots with a band gap of 1.24 eV~2.07 eV to achieve complete absorption of blue light and emission of red light.
[0011] In some embodiments of the present invention, the molar ratio of the quantum dots to the ligands is 1:(1-20), preferably 1:(5-10), for example, the molar ratio is 1:1, 1:3, 1:5, 1:7, 1:9, 1:12, 1:15, 1:17, 1:20, etc. The inventors have found that the molar ratio of quantum dots to ligands is controlled within the above range, which can effectively improve the dispersibility, stability, fluorescence and biocompatibility of quantum dots.
[0012] In some embodiments of the present invention, the ligand includes at least one of oleylamine, oleic acid, liquid alkyl primary amines having 6 to 20 carbon atoms, phenylethylamine, di-n-propylamine, diisocyanate hexane, trihydroxypropyl phosphine, tributyl phosphine, triethyl phosphine, trioctyl phosphine, diphenyl phosphine, triphenyl phosphine, trioctyl phosphine oxide, tripentyl phosphine, stearyl sulfobetaine, thioglycolic acid, mercaptopropionic acid, triphenylmethanethiol, N,N-dimethyldodecylaminobutyrate, sulfobetaine, choline phosphate, γ-amino acid, 2-ethylhexanoic acid, hexadecyl sulfobetaine, n-dodecyl-N,N-dimethylglycine, lauryl dimethyl sulfobetaine, γ-butyl betaine, aminosulfobetaine, octylphosphonic acid, tetradecylphosphonic acid, octadecylphosphonic acid, quaternary ammonium bromide, hexyl phosphonate, tri-n-octylphosphine, 2,2'-iminodibenzoic acid, and 2-aminoterephthalic acid.
[0013] In some embodiments of the present invention, the quantum dots include at least one of CdSe quantum dots, CdS quantum dots, CdTe quantum dots, ZnSe quantum dots, ZnTe quantum dots, PbS quantum dots, PbSe quantum dots, and CuInS2 quantum dots.
[0014] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned quantum dot contact lens. According to an embodiment of the present invention, the method comprises: (1) After mixing a first quantum dot precursor and a ligand in a first solvent, a second quantum dot precursor is added to the first solvent to undergo a chemical reaction to obtain ligand-modified quantum dots; (2) dispersing the ligand-modified quantum dots into a second solvent to obtain a quantum dot colloidal solution; (3) The quantum dot colloidal solution is mixed with a contact lens polymer material and then solidified in a mold to obtain a quantum dot contact lens.
[0015] The hot injection method is used to quickly inject the precursor solution into the hot reaction solution at a specific temperature, so that the supersaturation of the solution increases instantly, and the nanocrystals quickly nucleate and grow. As nucleation proceeds, the supersaturation of the solution decreases, nucleation stops, and the reaction enters the crystal nucleus growth stage. The separation of the nucleation and growth stages makes the growth state of each grain basically consistent, ensuring the monodispersity of the product. The ligand has a regulating effect on this reaction rate, and can also form a bond with the surface atoms of the synthesized quantum dots and adsorb on the surface of the quantum dots, maintaining the monodispersity between the quantum dots and avoiding spontaneous agglomeration between quantum dots due to high surface energy. The hot injection method does not require high temperature and high pressure conditions, which reduces the requirements for equipment, and because the reaction conditions are easy to control and mild, the crystal growth rate is fast, and nano quantum dot crystals of different sizes, morphologies and structures can be prepared. Therefore, the above method can effectively modify the ligand on the quantum dots, prepare ligand-modified quantum dots of suitable size, thereby improving the blue light absorption and red light emission performance of the contact lens.
[0016] In some embodiments of the present invention, in step (1), the system temperature in which the chemical reaction occurs is 80°C to 350°C. For example, the temperature is 80°C, 150°C, 200°C, 250°C, 300°C, 350°C, etc. Controlling the temperature within the above range can improve the preparation efficiency of quantum dots.
[0017] In some embodiments of the present invention, the first solvent includes at least one of octadecene and liquid paraffin.
[0018] In some embodiments of the present invention, the ligand-modified quantum dots prepared in step (1) are cleaned with a solvent such as ethyl acetate, methyl acetate, acetone, ethanol, methanol, chloroform, or dichloromethane to remove impurities.
[0019] In some embodiments of the present invention, in step (2), the concentration of ligand-modified quantum dots in the quantum dot colloidal solution is 0.1 mg / mL to 500 mg / mL, preferably 10-60 mg / mL. For example, the concentration of quantum dots is 0.1 mg / mL, 10 mg / mL, 30 mg / mL, 50 mg / mL, 70 mg / mL, 100 mg / mL, 120 mg / mL, etc. The inventors have found that controlling the concentration of ligand-modified quantum dots within the above range can ensure that the quantum dot solution and the original contact lens solution are mixed evenly, while also ensuring the stability of the contact lens when the mold is peeled off after curing, as well as the luminous intensity of the finished product.
[0020] In some embodiments of the present invention, the first solvent includes at least one of deionized water, hexane, and toluene.
[0021] In some embodiments of the present invention, in step (3), the volume ratio of the quantum dot colloid solution to the contact lens polymer material is less than 1:50. The optimal volume ratio is 1:100. The inventors have found that the volume ratio of the quantum dot colloid solution to the contact lens polymer material is controlled within the above range and can be adjusted according to the quantum dot concentration. Since the concentration and volume jointly determine the transparency and luminescence properties of the finished contact lens, when we use a 50 mg / mL concentration of quantum dot solution mixed with the original contact lens solution in a volume ratio of 1:100, the transparency does not affect the wearing field of vision, and it also has a suitable luminescence intensity in the 630-650 nm band.
[0022] In some embodiments of the present invention, the contact lens polymer material includes at least one of silicone, polymethyl methacrylate (PMMA), polyethersulfone (Polysulfone), polyhydroxyethyl methacrylate (PHEMA) and mixed materials thereof, and polydimethylsiloxane (PDMS).
[0023] The present invention has at least the following technical effects: (1) After the quantum dot contact lens of the present invention is worn, the quantum dots inside the contact lens absorb harmful blue light and emit fluorescence in the red band and its adjacent bands, which is incident into the wearer's eyes to achieve the effect of improving vision.
[0024] (2) The quantum dots of the present invention are modified by ligands and suitable solvents, which can significantly improve the dispersibility of quantum dots in the main material of contact lenses, thereby effectively avoiding the agglomeration of quantum dots, causing the inactivation of quantum dots, and improving the fluorescence stability of quantum dots. At the same time, the passivation effect of the ligand can reduce the surface defects of quantum dots, inhibit the non-radiative recombination of carriers, and improve the stability and fluorescence properties of quantum dots. At the same time, compared with unmodified quantum dots, quantum dots modified by ligands have excellent biocompatibility.
[0025] (3) The present invention adopts the hot injection method to prepare ligand-modified quantum dots, which can prepare nano-quantum dot crystals with suitable size, morphology and structure, thereby improving the blue light absorption performance and red light emission performance of contact lenses. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the present invention or the prior art, a brief introduction is given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Figure 1 This is a physical picture of the colloidal quantum dot solution of Example 1 of the present invention and a physical picture under ultraviolet irradiation; Figure 2 The actual picture of the contact lens mixed solution of Example 1 of the present invention and the actual picture under ultraviolet irradiation; Figure 3 is a color diagram of the contact lens mixed solution of Example 1 of the present invention observed under a fluorescence microscope; Figure 4 The physical picture of the quantum dot contact lens prepared in Example 1 and the conventional contact lens without quantum dots and the physical picture after ultraviolet irradiation; Figure 5 is a comparison diagram of absorption spectra of the colloidal quantum dot solution, the original contact lens polymer material solution and the contact lens mixed solution of Example 1; Figure 6 is a fluorescence spectrum comparison diagram of the quantum dot solution and the quantum dot contact lens solution of Example 1; Figure 7 is a diagram of a contact lens with different red light emission area patterns according to an embodiment of the present invention; Figure 8 is a fluorescence spectrum comparison diagram of the quantum dot solution and the quantum dot contact lens solution of Example 2; Fig. 9 This is the actual contact lens containing quantum dots after molding in Example 2; Fig.10 This is the actual quantum dot contact lens prepared in Comparative Example 1; Fig.11 This is the actual quantum dot contact lens prepared in Comparative Example 2. DETAILED DESCRIPTION
[0028] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0029] Example 1 (1) Preparation of oleic acid-modified CdSe quantum dots: The precursor 1 used was cadmium oleate (Cd-OA), the precursor 2 was trioctylphosphine selenide (TOP-Se), the ligand was oleic acid (OA), and the reaction solvent was octadecene (ODE). First, ODE, OA, and Cd-OA were mixed at room temperature, and then vacuumed for about 45 min-60 min and heated to about 100 °C at the same time, in order to remove the residual oxygen and moisture in the reaction system. Then, nitrogen was introduced, the reaction temperature was raised to 220 °C (i.e., the reaction temperature), and TOP-Se was quickly injected. A chemical reaction occurred immediately to generate CdSe quantum dots. After about 5 min of reaction, the reaction system was quickly cooled to room temperature using an ice bath, and the synthesis of oleic acid-modified CdSe quantum dots was completed. The particle size of the CdSe quantum dots was 6 nm, the band gap of the CdSe quantum was 1.96 eV, and the molar ratio of the CdSe quantum dots to OA was 1:5.
[0030] (2) The oleic acid-modified CdSe quantum dots prepared above are washed with ethyl acetate solvent, and impurities are separated by high-speed centrifugation. Then, the oleic acid-modified CdSe quantum dots after impurity removal are dispersed in n-hexane to obtain a colloidal quantum dot solution, wherein the concentration of the oleic acid-modified CdSe quantum dots in the colloidal quantum dot solution is 10 mg / mL.
[0031] (3) Preparation of contact lenses: Prepare the original polymer material solution of contact lens PDMS system (base material (dimethylsiloxane) and curing agent (SYLGARD™184Silicone Elastomer Kit) are mixed in a volume ratio of 5:1). Add 1 µL of colloidal quantum dot solution to 100 µL of PDMS system contact lens solution to obtain a contact lens mixed solution. Place the mixed solution in a contact lens mold and cure it under ultraviolet light for 15 min. Then take it out or put it in an oven at 60°C for 3 h to obtain a quantum dot contact lens.
[0032] Figure 1 The colloidal quantum dot solution of Example 1 is a physical picture and a physical picture under ultraviolet irradiation; Figure 2 The following are the physical pictures of the contact lens mixed solution of Example 1 and the physical pictures under ultraviolet irradiation. Figure 1 and Figure 2 It can be seen that the addition of the contact lens polymer material of the present application does not affect the fluorescence properties of the quantum dots themselves.
[0033] Figure 3 This is the color of the contact lens mixed solution of Example 1 observed under a fluorescent microscope. It can be seen that the overall color is bright red, showing the stimulating effect of the contact lens mixed solution, proving that it can indeed emit beneficial light in the red range that is good for the eyes.
[0034] Figure 4The following are the physical pictures of the quantum dot contact lens (label 1) prepared in Example 1 and the conventional contact lens without quantum dots (label 2) and the physical pictures after ultraviolet irradiation. Figure 4 It can be seen that compared with existing contact lenses, the quantum dot contact lenses of the present application can release red light.
[0035] Figure 5 is a comparison diagram of the absorption spectra of the colloidal quantum dot solution, the original contact lens polymer material solution and the contact lens mixed solution of Example 1. Figure 5 It can be seen that after the quantum dot solution is mixed with the original solution of the contact lens polymer material, the absorbance in the visible light range is higher than that of the two solutions alone, proving that our contact lenses embedded with quantum dots have a more sensitive absorption effect on light.
[0036] Figure 6 is a fluorescence spectrum comparison diagram of the quantum dot solution and the quantum dot contact lens solution of Example 1. Figure 6 It can be seen that after the quantum dot solution is mixed with the original contact lens solution, the fluorescence peak position is red-shifted, but the emission wavelength is still within the red light range and the fluorescence intensity is not significantly weakened.
[0037] The present application can also use the contact lens mixed solution of Example 1 to prepare contact lenses with different red light emitting area patterns, for example, Figure 7 .
[0038] Example 2 The difference between Example 2 and Example 1 is: In step (1), by changing the reaction time in step (1), the reaction system was quickly cooled to room temperature using an ice bath after about 4 minutes of reaction, and the quantum dot size was about 5.5 nm.
[0039] In step (3), a PHEMA system solution (1 mL of hydroxyethyl methacrylate, 15 µL of ethylene glycol dimethacrylate, and 9.5 µL of 2-hydroxy-2-methylpropiophenone) was used.
[0040] The fluorescence spectra comparison of the quantum dot solution of Example 2 and the quantum dot contact lens solution are shown in FIG. Figure 8 As shown, from Figure 8 It can be seen that the fluorescence intensity is quenched to a certain extent, which is not as good as that of the PDMS system in Example 1, but it still has good fluorescence characteristics, which can be improved by further optimization of the quantum dot material system in the later stage. It also shows that the PDMS system has greater potential advantages than the PHEMA system in the preparation of quantum dot contact lenses. The actual contact lens containing uniformly distributed quantum dots after molding is shown in FIG. Fig. 9 shown.
[0041] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is: In step (2), the oleic acid-modified CdSe quantum dots prepared above are washed with ethyl acetate solvent, and impurities are separated by high-speed centrifugation. Then, the oleic acid-modified CdSe quantum dots after impurities are removed are dispersed in n-hexane to obtain a colloidal quantum dot solution. The obtained colloidal quantum dot solution is transferred to an aqueous solution containing an aqueous phase ligand (including thioglycolic acid, mercaptopropionic acid, sodium 3-mercaptopropane sulfonate, sodium 2-mercaptoethane sulfonate, etc., and thioglycolic acid is used in this comparative example), and stirring is continued until the ligand exchange is completed. The quantum dots converted from oil phase ligands to aqueous phase ligands will precipitate from the organic solvent and disperse in the aqueous solution. The impurities are separated by high-speed centrifugation, and then the CdSe quantum dots modified with aqueous phase ligands after impurities are removed are dispersed in deionized water to obtain aqueous phase colloidal quantum dot solutions of different concentrations.
[0042] Comparative Example 1: The contact lens prepared by using CdSe quantum dots modified with aqueous ligands is shown in FIG. Fig.10 As shown, from Fig.10 It can be seen that the CdSe quantum dots modified with water-phase ligands cannot be mixed evenly with the PDMS system, and the prepared quantum dot contact lenses contain a large number of quantum dot aggregates.
[0043] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is: In step (3), when preparing the contact lens, 5 µL of the colloidal quantum dot solution is added to 100 µL of the PDMS system contact lens solution to obtain a contact lens mixed solution (i.e., 1:20, greater than 1:50), and the mixed solution is placed in a contact lens mold, and cured under ultraviolet light for 15 min, then taken out or placed in an oven at 60°C for 3 h to obtain a quantum dot contact lens.
[0044] The obtained quantum dot contact lens is as follows Fig.11 As shown, from Fig.11 It can be seen that due to the addition of too much colloidal quantum dot solution, it was ultimately unable to solidify and form.
[0045] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A quantum dot contact lens, characterized in that: The invention comprises a contact lens polymer material body, wherein quantum dots are embedded and distributed in the contact lens polymer material body, and the quantum dots are modified by ligands.
2. The quantum dot contact lens according to claim 1, characterized in that: The particle size of the quantum dots is 1 nm to 20 nm.
3. The quantum dot contact lens according to claim 1 or 2, characterized in that: The band gap of the quantum dots is 1.24 eV~2.07 eV.
4. The quantum dot contact lens according to claim 1 or 2, characterized in that: The molar ratio of the quantum dots to the ligand is 1:(1-20).
5. The quantum dot contact lens according to claim 1 or 2, characterized in that: The ligand comprises at least one of oleylamine, oleic acid, liquid alkyl primary amine having 6 to 20 carbon atoms, phenylethylamine, di-n-propylamine, diisocyanate hexane, trihydroxypropylphosphine, tributylphosphine, triethylphosphine, trioctylphosphine, diphenylphosphine, triphenylphosphine, trioctylphosphine oxide, tripentylphosphine, stearyl sulfobetaine, thioglycolic acid, mercaptopropionic acid, triphenylmethanethiol, N,N-dimethyldodecylaminobutyrate, sulfobetaine, choline phosphate, γ-amino acid, 2-ethylhexanoic acid, hexadecyl sulfobetaine, n-dodecyl-N,N-dimethylglycine, lauryldimethylsulfobetaine, γ-butylbetaine, aminosulfobetaine, octylphosphonic acid, tetradecylphosphonic acid, octadecylphosphonic acid, quaternary ammonium bromide, hexyl phosphonate, tri-n-octylphosphine, 2,2'-iminodibenzoic acid, and 2-aminoterephthalic acid; And / or, the quantum dots include at least one of CdSe quantum dots, CdS quantum dots, CdTe quantum dots, ZnSe quantum dots, ZnTe quantum dots, PbS quantum dots, PbSe quantum dots, and CuInS2 quantum dots.
6. A method for preparing the quantum dot contact lens according to any one of claims 1 to 5, characterized in that: include: (1) After mixing a first quantum dot precursor and a ligand in a first solvent, a second quantum dot precursor is added to the first solvent to undergo a chemical reaction to obtain ligand-modified quantum dots; (2) dispersing the ligand-modified quantum dots into a second solvent to obtain a quantum dot colloidal solution; (3) The quantum dot colloidal solution is mixed with a contact lens polymer material and then solidified in a mold to obtain a quantum dot contact lens.
7. The method according to claim 6, characterized in that: In step (1), the temperature of the system in which the chemical reaction occurs is 80°C to 350°C; And / or, the first solvent includes at least one of octadecene and liquid paraffin.
8. The method according to claim 6, characterized in that: In step (2), the concentration of ligand-modified quantum dots in the quantum dot colloidal solution is 0.1 mg / mL to 120 mg / mL; And / or, the first solvent includes at least one of deionized water, hexane, and toluene.
9. The method according to claim 6, characterized in that: In step (3), the volume ratio of the quantum dot colloidal solution to the contact lens polymer material is less than 1:
50.
10. The method according to claim 6, characterized in that: The contact lens polymer material comprises at least one of silicone resin, polymethyl methacrylate, polyethersulfone, polyhydroxyethyl methacrylate and a mixture derived therefrom, and polydimethylsiloxane.
Citation Information
Patent Citations
CsPbX3 quantum dot, CsPbX3 / SiO2 (silicon dioxide) composite quantum dot, preparation method and backlight module
CN106830060A
Quantum dot polymer compound and preparation method thereof
CN111875896A
Anti-blue light quantum dot resin lens and preparation method thereof
CN113637279A
Silica-coated quantum dot-doped matrix photochromic resin lens and method
CN117089187A
Anti-blue anti-reflection quantum dot compound and quantum dot light conversion device
CN117511548A